THE IMPACT OF LOCAL REVENUE AND EXPENDITURES ON FINANCIAL PERFORMANCE IN RIAU PROVINCE 2022-2025 - M. Ilham Sapi’i; Yusriwarti Yusriwarti; Muhammad Fauzan (Indragiri Research Center (ingreat), 2026)
This study analyzes the influence of Local Own-Source Revenue (PAD), Personal Expenditure, and Capital Expenditure on the Financial Performance of District/City Local Governments in Riau Province for the 2022-2025 period. The underlying phenomena are PAD growth reaching 70.05 percent but capital expenditure contracting by minus 26.07 percent, revenue realization only 86.7 percent of the target, operating expenditure dominance of 89.09 percent, and APBD deficits in five regencies. This study uses secondary data from 12 regencies or cities, resulting in 48 observations. Analysis includes descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test and coefficient of determination using SPSS Version 25. The results show that simultaneously the three variables have a significant effect on financial performance with a contribution of 26.6 percent. Partially, PAD has a significant negative effect (t = -2.799, sig. 0.008), personal expenditure has no significant effect (t = -0.130, sig. 0.897), while capital expenditure has a significant positive effect (t = 3.265, sig. 0.002). Local governments need to improve revenue and capital expenditure realization and streamline personnel expenditure.